Self-compassion in Nursing Students and Its Correlations With Moral Intelligence, and Moral Perfectionism: A Cross-Sectional Study - Sajad Yarahmadi; Monir Nobahar; Nayyereh Raiesdana; Elham Shahidi Delshad (SAGE Open Nursing)
Introduction Self-compassion plays a vital role in maintaining mental health. Evidence suggests that enhancing morality-related constructs can improve self-compassion among nursing students. This study examines the predictors of self-compassion in nursing students and explores its relationship with moral intelligence and moral perfectionism. Methods This cross-sectional, multicenter study was conducted between January and March 2022. Undergraduate nursing students from three Iranian universities—Tehran University of Medical Sciences, Lorestan University of Medical Sciences, and Semnan University of Medical Sciences—were surveyed using the Self-Compassion Scale, Moral Intelligence Questionnaire, and Moral Perfectionism Scale. Correlation analyses and stepwise linear regression were employed to assess the relationships between variables. Results A total of 250 nursing students participated, reporting moderate self-compassion levels ( M  = 37.19, SD  = 5.02). Self-compassion was positively correlated with moral intelligence ( r  = .33, p  < .001) and moral perfectionism ( r  = .23, p  < .001). Forgiveness emerged as a significant predictor of self-compassion (β = 0.33, p  < .001). Conclusion This study underscores the significance of moral intelligence and moral perfectionism in fostering self-compassion among nursing students. Integrating forgiveness and ethical development into nursing education could enhance professional competence and compassionate care delivery.